The efficacy of internet-based cognitive behavior therapy for psychological health and quality of life among breast cancer patients: a systematic review and meta-analysis - Lin, Tang; Ping, Yin; Jing, Cai Ming; Xu, Zhi Xiao; Ping, Zhu (Frontiers in Psychology, 2025)
ObjectiveTo systematically investigate the effect of Internet-based cognitive-behavioral therapy (ICBT) on depression, anxiety, fatigue and quality of life (QOL) in patients with breast cancer (BC).MethodsA systematic review with meta-analysis and qualitative evidence synthesis was performed. Ten databases, including PubMed, Web of Science, EMBASE, the Cochrane Library, CINAHL, JBI Chinese Biomedical database (CBM), China National Knowledge Infrastructure (CNKI), VIP, and Wanfang, were searched from the start till August 2023. Published studies in English or Chinese were eligible for randomized and clinical controlled trials determining the efficacy of ICBT among BC survivors. The quality of the evidence was evaluated at the study level and the outcome level.ResultsIn total, 11 clinical trials on 1,307 patients with BC (ICBT: 671, control: 636) were systematically reviewed. We found that ICBT is effective in alleviating psychological distress in BC survivors, and the quality of all studies was moderate. The meta-analysis indicated that ICBT affected primary outcomes of anxiety (standardized mean difference [SMD] = −0.71, 95% confidence interval [CI]: −1.19, −0.24, p < 0.0001), depression (SMD = −0.67, 95% CI: −1.07, −0.27, p < 0.0001), fatigue (SMD = −1.23, 95% CI: −2.37, −0.08, p < 0.0001) and QOL (SMD = 0.79, 95% CI: 0.21, 1.37, p < 0.00001).ConclusionThis meta-analysis indicates that ICBT, as a type of psychosocial rehabilitation, can mitigate the incidence of depression, anxiety, and fatigue and improve the quality of life among patients with BC. Nevertheless, the effect is not distinct, and multi-centered randomized controlled trials with larger cohorts are warranted to verify the effectiveness of ICBT.